Pelatihan Dan Pengembangan Kualitas Bermusik Gereja Di Jemaat GMIT Gunung Zalmon Labuan Bajo, Klasis Flores Barat, Nusa Tenggara Timur: - - Huka, Relin (Institut Agama Kristen Negeri Kupang, 2024)
The Music Service is an important part of the liturgy within the Evangelical Christian Church in Timor (GMIT). In this regard, it is necessary to carry out a training process to improve the quality of music, both for music players and other liturgy supporters. This process requires cooperation between various parties who have responsibilities and a desire to develop the quality of church music. IAKN Kupang, in this case the Faculty of Christian Religious Arts, also has a role in looking at the phenomena experienced by GMIT so that through coaching activities carried out through Community Service it can provide positive value for the development of church music within GMIT. Congregational singing, which is also something that is very dominant in worship, must be managed well so that worship can be of high quality